A design based research study on differentiated integer instruction using diagnostic assessment - Siahaan, Meiva Marthaulina Lestari; Fitriani; Laja, Yosepha Patricia Wua; Hijriani, Lailin (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purposes: This study aims to design instruction for integer learning using the GASING method based on learning needs. Method: The participants were 79 fifth-grade students from three schools in a sub-district. The study employed design-based research in three phases; preliminary design, teaching experiment, and retrospective analysis. Data were analyzed through cognitive diagnostic assessment, skills analysis, and error analysis to identify students’ learning needs and develop learning instruction. Findings: The findings revealed that most students were at the cognitive levels of remembering and understanding when solving problems related to integer properties, number order, place value, and contextual situations. Their numeracy literacy skills were generally low, and they demonstrated conceptual, procedural, and operational errors. Based on these diagnostic results, a learning design using the GASING method supported by interactive visual aids was developed. The design emphasizes number sequences through number lines, ascending and descending order, comparing integers, and solving contextual problems involving ordered numbers. For the concept of place value, the design includes activities such as comparing integers, reading and constructing numbers, understanding integer properties, and determining place value. Significance: These findings suggest that teachers should integrate context-based instruments into daily classroom instruction to strengthen students’ conceptual understanding and problem-solving skills.